Clinical-epidemiological profile of women undergoing oncological treatment for invasive ductal breast carcinoma (Research, Society and Development, 2021)
The aim of this study was to describe the clinical-epidemiological profile of women undergoing oncological treatment for invasive ductal breast carcinoma. This is a cross-sectional, descriptive and quantitative study carried out by data collection from clinical records of women undergoing breast cancer treatment in a private oncology service, considering sociodemographic and clinical variables. 125 women who met the proposed inclusion criteria were identified. Most of the patients were from Sergipe (71,2%), black or mixed (65,6%), with a partner (56%) and with a mean age of 53,5±11,4 years. Of these, 80,8% had no higher education and 77,6% had family income between one and three minimum wages. All patients underwent chemotherapy, 64,8% radical mastectomy and 36% radiotherapy. In addition, 32,8% showed changes in self-image, 24,8% in self-esteem, 64,8% signs of anxiety and 49,6% depressive symptoms. In addition, 40% had systemic arterial hypertension. The clinical-epidemiological profile of women with invasive ductal breast carcinoma described is wide and has important sociodemographic components. Cancer treatment can trigger clinical changes relevant to the health, well-being and quality of life of these patients.